The relationship between values of employees working for public institutions with the level of job satisfaction: a research in Bartin province - Esen, Şaban; Gülatar, Fazilet; Esen, Şaban (Zonguldak Bülent Ecevit Üniversitesi, 2018)
This study examines the relationship between the values attributed to quality, innovation, cooperation and participation in the decisions terms by the public institutions’ employees with job satisfaction. The values attributed by the employees to aforementioned terms are defined as “job-related values”. In this context, the opinions of the 761 people working at the university, municipality, governorship and state hospital in Bartın were collected using a questionnaire. The data obtained were analyzed via both descriptive and generalizing statistical methods. The findings of analyses show that there is a relationship between workplace values of public institution employees and their level of job satisfaction.

Bu çalışmada kamu kurumu çalışanlarının kalite, yenilikçilik, işbirliği ve kararlara katılım kavramlarına atfettikleri değerlerin, çalışanların iş tatmini ile ilişkisi incelenmiştir. Çalışanların sözü edilen kavramlara ilişkin atfettikleri değerler “işe ilişkin değer” olarak tanımlanmıştır. Bu bağlamda Bartın ilinde faaliyet gösteren üniversite, belediye, valilik ve devlet hastanesinden 761 çalışanın görüşleri anket ile toplanmıştır. Elde edilen veriler hem tanımlayıcı hem de genelleyici istatistiksel yöntemlerle analiz edilmiştir. Analiz sonuçları göstermektedir ki kamu kurumu çalışanlarının iş değerleri ile işlerinden elde ettikleri tatmin düzeyi ilişkilidir.
Keywords: İş tatmini; Job satisfaction